Making one’s point of view: Approaching literary analysis and critical theory through David Bowie’s “Lady Stardust" (Altre Modernità, 2022)
Some years ago I used a Bowie song, “Lady Stardust”, for a warm-up activity at the beginning of a BA course in English Literature focusing on gender issues from the Romantic Age to the present. Resulting from that didactic experiment, this article aims at proposing ways in which Bowie’s song and its lyrics can help students approach the interconnections between textual analysis and critical theory (Gender and Cultural Studies) by rooting them into language and social history. Furthermore, through reference to Sound Studies and ‘aurality’, it also invites the reader to reflect on how music can offer a valuable contribution for approaching literary and cultural studies, involving some pedagogical reflections inspired by Elena Madrussan’s recent volume Formazione e musica: L’ineffabile significante nel quotidiano giovanile (Mimesis 2021).
Keywords: Bowie; Gender Studies; music and literature; Sound Studies; Cultural Studies; textual analysis